Answer:
<u><em>(-4, -2)</em></u>
Step-by-step explanation:
<u><em>When using the elimination method, </em></u><u><em>we combine the equations to get one.</em></u><u><em> To combine them, we have to </em></u><u><em>find a term with a number that is either positive or negative to the other, example : -6y and 6y, or 4x and -4x. We then take them and combine both equations to get one.</em></u><u><em> </em></u><u><em>Becuase they are the same, they simply cancel each other out.</em></u>
<u><em>9x - 9y = -18</em></u>
<u><em>-6x + 9y = 6</em></u>
<u><em>3x = -12</em></u>
<u><em>Divide both sides by 3 to get x alone</em></u>
<u><em>x = -4</em></u>
<u><em>Now, to find the y value, we can now </em></u><u><em>plug in what we found for x.</em></u>
<u><em>9(-4) - 9y = -18</em></u>
<u><em>-36 - 9y = -18</em></u>
<u><em>Add 36</em></u>
<u><em>-9y = 18</em></u>
<u><em>Divide by -9</em></u>
<u><em>y = -2</em></u>
<u><em>Therefore making the solution,</em></u><u><em> (-4, -2)</em></u>